Culinary Tour A La Millennials (An Exploratory Study in Ubud) - Ni Ketut Wiwiek Agustina (Institut Pariwisata dan Bisnis Internasional, 2021)
Ubud as one of the wellknown tourists’ destinations in Bali Province, currently is developing the potency on culinary for tourism. Nowadays Ubud is also becoming the interests of millennial tourists to visit. Millenn ial tourists represent 27 % of the global population or around 2 billion people. On average, they take 35 days of vacation each year with the typical of preferring experience the most. Therefore, this research is designed by exploratory study approach and the aims are to analyze and identify the interests of millennial tourists to visit Ubud for the purpose of tasting and enjoying culinary for the sake of tourism. Primary data is collected using semi-structured interviews with respondents as many as 30 (thirty) millennial visitors or tourists in Ubud. Through a descriptive method with a qualitative approach, this research explores millenials’ thoughts and motivation of culinary tourists in Ubud. For the result, this study indicates millennials tourists’ respondents have a high interest in culinary tours. Ubud is considered to offer a large selection of local culinary delights of good taste and quality; calm, comfortable, and nice view and atmosphere; and is a favorite destination for tourists. Sources of information about culinary tours in Ubud are recommendations from friends / relatives and social media. This study also includes exploratory observations regarding the food menu, location, facilities, and security in Ubud District. For wider perspectives on culinary tours a la millennials, further research is encouraged in other areas and interests.